PERAN SASTRA DALAM MEMPERTAHANKAN IDENTITAS BUDAYA PADA MASA PENJAJAHAN - Devi Angelia (Journal of Linguistics, Literature, Culture and History, 2025)
During the colonial period, Indonesian society was divided into rigid social classes: aristocrats, priyayi, and commoners. The aristocrats and priyayi often collaborated with the colonial government, while the commoners, particularly farmers and laborers, lived in poverty due to exploitative policies such as the forced cultivation system. This study explores the role of literature in preserving and revitalizing a nation's cultural identity amidst colonial hegemony, aiming to illustrate its contribution as a medium for preserving values and traditions. This study uses a qualitative approach with literary text analysis as its primary method, focusing on the meaning and structure of literary works from the Dutch colonial period. Data collection was conducted using library research techniques and secondary sources such as books, scientific articles, and related documents. The study concludes that literature during the colonial period functioned as a tool of resistance and social criticism, recording the nation's history of suffering and struggle, while simultaneously building national identity and awareness. Literature created narratives that provided moral strength to the people in the face of colonial oppression and helped maintain local culture and values as the foundation of the nation.